SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA BEASISWA PADA SMK BERSAMA BERASTAGI DENGAN METODE TOPSIS - Amsal Prima Tarigan; Denny M. Rajagukguk (UPPM, 2019)
Today all matters will be related to the ease of processing data without taking a long time, thereforethe solution is the formation of a computerized system to find the best results. Berastagi JointVocational School is a vocational high school located at Simpang Ujung Aji No 1, Jalan JaminGinting, Berastagi District, Karo Regency. Scholarships are gifts in the form of financial assistancegiven to individuals, students or students that are used for the continuation of education beingpursued. Every year the school provides scholarships for outstanding students. The author builds asystem that will assist schools in selecting students who are entitled to receive scholarships. Thesystem is built in the form of a decision making system using the topsis method. The criteria used forthis decision-making system are report card grades, absenteeism, tests of academic potential andorganizational activity. The system was built using the PHP programming language. Students whoare entitled to get a scholarship are students who have high grades from the system calculationresults.